NEPHRUTIX: A randomized, double-blind, placebo vs Rituximab-controlled trial assessing T-cell subset changes in Minimal Change Nephrotic Syndrome. (March 2018) - Boumediene, Ahmed; Vachin, Pauline; Sendeyo, Kelhia; Oniszczuk, Julie; Zhang, Shao-yu; Henique, Carole; Pawlak, Andre; Audard, Vincent; Ollero, Mario; Guigonis, Vincent; Sahali, Djillali
Abstract: Minimal-change nephrotic syndrome (MCNS) is an immune-mediated glomerular disease. We have analyzed the modifications on T-cell subsets in twenty-three patients who were highly steroid/calcineurin inhibitor and/or mycophenolate mofetil-dependent for frequently relapsing nephrotic syndrome (FRNS) and who were enrolled in a multicenter, double-blind, randomized, placebo vs Rituximab-controlled trial. Patients with FRNS entered the trial at remission and were randomly assigned to receive either Rituximab or placebo. In both groups, patient blood samples were analyzed at inclusion and then monthly until six months post-perfusion. Disclosure of patient's allocation code occurred in relapse or at the end of the trial. All patients under placebo displaying relapse were subsequently treated with Rituximab. Despite the significant decrease of immunosuppressive drugs, remission was maintained in all patients included in the Rituximab group, except one (n = 9/10). On the other hand, relapses occurred within a few weeks (means ≈ 7.3 weeks) in all patients receiving placebo (n = 13). At inclusion, before rituximab therapy, the frequency of different T-cell subsets were highly similar in both groups, except for CD8 + and invariant TCRVα24 T-cell subsets, which were significantly increased in patients of the Placebo group ((p = 0, 0414 and p = 0.0428, respectively). Despite the significant decrease of immunosuppressive drugs, remission was maintained in all patients included in the Rituximab group (n = 10), except one. Relapses were associated with a significant decrease in CD4 + CD25 high FoxP3 high Tregulatory cells (p = 0.0005) and IL2 expression (p = 0.0032), while CMIP abundance was significantly increased (p = 0.03). Remissions after Rituximab therapy were associated in both groups with significant decrease in the frequency of CD4 + CD45RO + CXCR5 +, invariant natural killer T-cells (INKT) and CD4 − CD8 − (double-negative, DN) T-cells expressing the invariant Vα24 chain (DN-TCR Vα24) T-cells, suggesting that MCNS involves a disorder of innate and adaptive immune response, which can be stabilized by Rituximab treatment. Highlights: MCNS is associated with low IL-2 production and a downregulation of Tregulatory cells. MCNS is an autoimmune disease, which can be stabilized by Rituximab treatment. Rituximab downregulates the double negative invariant T-cell subset (TCR DN-TCRα24).